1995
DOI: 10.1021/bi00002a004
|View full text |Cite
|
Sign up to set email alerts
|

Structural Basis for the Catalytic Activity of Aspartate Aminotransferase K258H Lacking the Pyridoxal 5'-Phosphate-Binding Lysine Residue

Abstract: Chicken mitochondrial and Escherichia coli aspartate aminotransferases K258H, in which the active site lysine residue has been exchanged for a histidine residue, retain partial catalytic competence [Ziak et al. (1993) Eur. J. Biochem. 211, 475-484]. Mutant PLP and PMP holoenzymes and the complexes of the latter (E. coli enzyme) with sulfate and 2-oxoglutarate, as well as complexes of the mitochondrial apoenzyme with N-(5'-phosphopyridoxyl)-L-aspartate or N-(5'-phosphopyridoxyl)-L-glutamate, were crystallized a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
31
0

Year Published

1999
1999
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(34 citation statements)
references
References 32 publications
3
31
0
Order By: Relevance
“…However, PLP is clearly bound to the active site. This is similar to what was described for a K258H mutant of chicken mitochondria AAT and E. coli AAT (Malashkevich, Jä ger et al, 1995). The density for PLP is strong, and the occupancy of PLP was refined to 0.88 and 0.89 in the two chains, with B factors that were very similar to those for the environment (Fig.…”
Section: Resultssupporting
confidence: 78%
“…However, PLP is clearly bound to the active site. This is similar to what was described for a K258H mutant of chicken mitochondria AAT and E. coli AAT (Malashkevich, Jä ger et al, 1995). The density for PLP is strong, and the occupancy of PLP was refined to 0.88 and 0.89 in the two chains, with B factors that were very similar to those for the environment (Fig.…”
Section: Resultssupporting
confidence: 78%
“…However, in all of these enzymes water molecules are believed to play no catalytic role; rather, they seem to contribute to the binding of the substrate. On the other hand, for the K258H variant of aspartate aminotransferase (18) it was suggested that the 1,3-prototropic shift catalyzed by this mutant protein is mediated by a water molecule. Water molecules have also been suggested as representing excellent candidates for the protonation of external aldimine of threonine aldolase with glycine (19).…”
Section: Discussionmentioning
confidence: 99%
“…These two enzymes do not show any mutual sequence similarity and have different folds and different enantiomeric selectivites. mAspAT is one of the most thoroughly characterized aminotransferases; in particular, the catalytic activity of its K258H variant lacking the PLP binding lysine residue has been explained on the basis of its crystal structure (27). DaAT has the same enantiomeric selectivity as 15A9.…”
Section: Resultsmentioning
confidence: 99%